Composite active material, preparation method and obtained lithium-iron disulfide battery positive plate

By using the core-shell structure composite active material of cobalt disulfide and iron disulfide, the problems of low discharge platform, high internal resistance and poor storage performance of lithium-ferrous disulfide battery are solved, and the battery performance is improved and the life is extended. .

CN119480963APending Publication Date: 2025-02-18HUIZHOU HUIDERUI LITHIUM BATTERY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411546677.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Lithium-ferrous disulfide batteries have problems such as low discharge platform, high internal resistance and poor storage performance, which are mainly caused by a single iron disulfide as an active material.

Method used

A core-shell structure composite active material of cobalt disulfide and iron disulfide was used to prepare an iron disulfide composite active material coated with cobalt disulfide by precipitation method, with a particle size of 12 to 20 μm.

Benefits of technology

It improves the discharge voltage platform of lithium-iron disulfide batteries, reduces internal resistance, improves pulse discharge performance and storage performance, and extends the battery life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005114601980000071
    Figure BDA0005114601980000071
  • Figure BDA0005114601980000072
    Figure BDA0005114601980000072
  • Figure BDA0005114601980000073
    Figure BDA0005114601980000073
Patent Text Reader

Abstract

The invention relates to the technical field of lithium battery manufacturing, in particular to a composite active material, a preparation method and an obtained lithium-iron disulfide battery positive plate. The composite active material is of a core-shell structure of cobalt disulfide and iron disulfide, the core-shell structure is characterized in that the cobalt disulfide is coated with the iron disulfide, the particle size of the cobalt disulfide is 2-5 microns, and the particle size of the composite active material is 12-20 microns. According to the method, the characteristic that physical and chemical properties of cobalt disulfide and iron disulfide are similar is utilized, cobalt disulfide is added in the iron disulfide preparation process through a precipitation method, cobalt disulfide serves as a precursor for preparing iron disulfide, cobalt disulfide serves as the center and extends outwards to synthesize iron disulfide, and then sulfur removal treatment is conducted. A lithium-iron disulfide battery positive plate prepared from the composite active material is high in conductivity and low in self-discharge rate, and a battery assembled by the positive plate material is low in internal resistance and excellent in storage performance. And the composite active material also improves the discharge platform of the battery and the pulse discharge performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium battery manufacturing, and in particular to a composite active material, a preparation method and a lithium-iron disulfide battery positive electrode sheet obtained. Background Art

[0002] As an important branch of lithium primary batteries, lithium-iron disulfide batteries have an increasingly strong demand in various fields, and the performance requirements are also getting higher and higher. At present, there are still some problems with lithium-iron disulfide batteries. The first is that the discharge platform of lithium-iron disulfide batteries is low, and the voltage of the battery drops rapidly at the end of discharge, resulting in insufficient battery capacity to meet the needs of some scenarios; second, due to the large resistivity of iron disulfide, the internal resistance of lithium-iron disulfide batteries is large, the discharge performance is poor, and the battery heats up severely, limiting its use scenarios. The third is that the storage performance is poor and cannot be used for devices that need to be started for a long time. The above three problems seriously affect the scope of application of lithium-iron disulfide batteries in many fields. The fundamental reason is that a single iron disulfide is used as an active material.

[0003] In order to improve the problems caused by single iron disulfide as an active material to the battery, people introduced cobalt disulfide materials with similar physical and chemical properties to iron disulfide. Cobalt disulfide is a high-performance electrode material, which is widely used in the field of lithium batteries because of its excellent conductivity and good charge and discharge properties. The resistivity of cobalt disulfide is 0.002Ω.cm, while the resistivity of iron disulfide is 0.036Ω.cm. In addition, the self-discharge rate of cobalt disulfide is low, so the long-term stability of the battery can be guaranteed. The high specific capacity and high conductivity of cobalt disulfide make it an ideal choice for positive electrode materials. The prior art mentions a composite positive electrode material of mechanical mixing of iron disulfide and cobalt disulfide, with an average particle size D50 of 5 to 10μm, which improves high-rate discharge performance and increases open circuit voltage. However, active materials with a smaller average particle size are easy to agglomerate in the positive electrode pulping process, resulting in uneven distribution of active materials in the positive electrode sheet, which in turn causes defects such as insufficient conductivity of the positive electrode sheet and uneven current density distribution during discharge. The prior art also mentions that a core-shell composite material with an inner core of iron disulfide and an outer shell of cobalt disulfide was prepared by a hydrothermal method to improve the discharge voltage platform of the thermal battery, increase the discharge capacity, and reduce the internal resistance. However, the high temperature and high pressure conditions of the hydrothermal method have high equipment requirements and are difficult, and have poor safety. Cobalt disulfide has poor chemical stability and is very easy to decompose in humid air. Using cobalt disulfide as an outer shell, cobalt disulfide is easy to decompose and increase the resistance polarization of the material and reduce the discharge capacity of the battery, thereby shortening the battery life. Summary of the invention

[0004] In view of the above technical defects, the present invention provides a composite active material with high chemical stability and a preparation method, thereby obtaining a lithium-iron disulfide battery positive electrode sheet with high safety and excellent electrical properties.

[0005] In order to solve the above technical problems, the technical solution of the present invention is: a composite active material, which is a core-shell structure of cobalt disulfide and iron disulfide, wherein the core-shell structure is iron disulfide coating cobalt disulfide, the particle size of cobalt disulfide is 2-5 μm, and the particle size of the composite active material is 12-20 μm. The structural difficulty of the composite active material lies in the control of the total particle size of the composite active material, which is controlled by the inner core particle size, the concentration and speed of adding raw materials during stirring to control the particle size and uniformity.

[0006] Further: The preparation method of the composite active material comprises the following steps: a. Add deionized water to cobalt disulfide and ferrous sulfate heptahydrate in a mass ratio of 1 to 2:10 to 25 and stir evenly, add 10 to 30% sodium persulfide solution by weight during stirring, soak and wash the precipitate after centrifugation of the mixture with deionized water for 2 to 4 times, and dry at 60 to 80°C to obtain an active material intermediate; b. Heat the intermediate product to 400 to 500°C in an argon atmosphere for 16 to 20 hours, cool it naturally, and sieve it to obtain a composite active material of iron disulfide with a particle size of 12 to 20 μm and coated with cobalt disulfide. The structural difficulty of the composite active material also lies in the fact that the proportion of the components of the composite active material is controlled by controlling the quality and concentration of the raw materials during the preparation process.

[0007] Preferably, the mass ratio of cobalt disulfide to ferrous sulfate heptahydrate in step a is 1:10-20. Preferably, the weight percentage of the sodium persulfide solution in step a is 10-20%. Preferably, in step a, the precipitate after centrifugation of the mixture is soaked and washed 3 times with deionized water, and dried at 70°C to obtain an active material intermediate product; in step b, the intermediate product is heated to 500°C in an argon atmosphere for 20 hours, and naturally cooled and sieved to obtain a composite active material of iron disulfide with a particle size of 12-20 μm and coated with cobalt disulfide. The preferred mass ratio and concentration help to control the particle size and uniformity of the composite active material. The preferred heating temperature and time help to improve the stability of the composite active material.

[0008] The present invention also provides a lithium-iron disulfide battery positive electrode sheet, which comprises an active conductive material, a conductive agent, a binder and a positive electrode additive. The active conductive material is the composite active material described in the claims of the present invention.

[0009] The lithium-iron disulfide battery positive electrode sheet is composed of 70-88wt% active conductive material, 4-10wt% conductive agent, 4-10wt% binder and 4-10wt% positive electrode additive in weight percentage.

[0010] Preferably, the weight percentage of the positive electrode sheet of the lithium-iron disulfide battery is 78wt% active conductive material, 10wt% conductive agent, 6wt% binder and 6wt% positive electrode additive. This ratio can make the composite active material show the best positive electrode conductivity, thereby improving the discharge capacity of the battery. The adhesion between the positive electrode slurry and the current collector is improved, and the adhesion can prevent the positive electrode from falling off during the storage of the battery, thereby improving the safety and storage performance of the battery.

[0011] The conductive agent is at least one of carbon nanotubes, graphite, graphene, graphite worms, Ketjen black and acetylene black.

[0012] The binder is at least one of polyvinylidene fluoride, polytetrafluoroethylene, polyacrylonitrile, carboxymethyl cellulose, polyimide and polyacrylate.

[0013] The positive electrode additive is at least one of glutaric anhydride, glycerol sulfite, ethylene sulfate, calcium oxide and silicon dioxide.

[0014] Compared with the prior art, the composite active material has a core-shell structure of cobalt disulfide and iron disulfide, wherein the core-shell structure is iron disulfide coated with cobalt disulfide, the particle size of the cobalt disulfide is 2 to 5 μm, and the particle size of the composite active material is 12 to 20 μm. Taking advantage of the similar physical and chemical properties of cobalt disulfide and iron disulfide, cobalt disulfide can stably exist in the preparation environment of iron disulfide. Therefore, we add cobalt disulfide to the process of preparing iron disulfide by precipitation method using ferrous sulfate heptahydrate and sodium persulfide. Cobalt disulfide will be used as a precursor for preparing iron disulfide, and iron disulfide will be synthesized by extending outward from cobalt disulfide as the center, and then desulfurization treatment will be carried out, and finally a composite active material of iron disulfide coated with cobalt disulfide can be prepared. Compared with the simple iron disulfide material, the present invention uses a precipitation method to prepare a cobalt disulfide-coated iron disulfide composite active material to replace the single iron disulfide active material. The average particle size is 12 to 20 μm, the preparation method is simple and safe, the outer layer of iron disulfide can provide good chemical stability for the active material, and retains the advantages of high conductivity and low self-discharge rate of the inner layer of cobalt disulfide. Through the synergistic effect of the two active substances in the composite active material, the internal resistance of the battery is reduced, the discharge voltage is increased, the pulse discharge performance is improved, and the battery storage performance is improved. The lithium-iron disulfide battery positive electrode sheet prepared with the composite active material has high conductivity and low self-discharge rate, and the battery assembled with the positive electrode sheet material has low internal resistance and excellent storage performance. The present invention solves the problems of low discharge platform, high internal resistance and poor storage of cylindrical lithium-iron disulfide batteries, and further promotes the application of cylindrical lithium-iron disulfide batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 11A discharge curves of AA-sized lithium-iron disulfide batteries prepared from the lithium-iron disulfide battery positive electrode sheet obtained from the composite active material of Example 1 and the lithium-iron disulfide battery positive electrode sheet of Comparative Example 1.

[0016] Figure 2 It is the 1A discharge curve of the battery prepared by the lithium-iron disulfide battery positive electrode sheet obtained from the composite active material of Example 1 and the lithium cobalt disulfide battery positive electrode sheet of Comparative Example 2. DETAILED DESCRIPTION

[0017] The main purpose of the present invention is to prepare a cobalt disulfide-coated iron disulfide composite active material by precipitation method to replace a single iron disulfide active material, with an average particle size of 12 to 20 μm, a simple and safe preparation method, an outer layer of iron disulfide can provide good chemical stability for the active material, and retain the advantages of high conductivity and low self-discharge rate of the inner layer of cobalt disulfide, and through the synergistic effect of the two active substances in the composite active material, the internal resistance of the battery is reduced, the discharge voltage is increased, the pulse discharge performance is improved, and the battery storage performance is improved. The lithium-iron disulfide battery positive electrode sheet prepared by the composite active material has high conductivity and low self-discharge rate, and the battery assembled by the positive electrode sheet material has low internal resistance and excellent storage performance. Thereby, the problems of low discharge platform, high internal resistance and poor storage of cylindrical lithium-iron disulfide batteries are solved, and the application of cylindrical lithium-iron disulfide batteries is further promoted.

[0018] Example 1

[0019] Preparation of composite active material: Add 2-5 μm cobalt disulfide and ferrous sulfate heptahydrate in a mass ratio of 1:10 into a beaker, add an appropriate amount of deionized water and stir evenly, slowly add 10% sodium persulfide solution during stirring, soak and wash the precipitate after centrifugation of the mixture with deionized water for 3 times, and dry at 70°C to obtain an active material intermediate. The intermediate product is heated to 500°C in an argon atmosphere for 20 hours, and naturally cooled and sieved to obtain iron disulfide coated with cobalt disulfide with an average particle size of 12-15 μm, i.e., a composite active material.

[0020] Preparation of positive electrode sheet of lithium-iron disulfide battery: The positive electrode slurry and positive electrode current collector are coated by a coating machine, and then baked, rolled, cut, and welded to form positive electrode sheet. The positive electrode slurry is composed of 78wt% composite active material, 6wt% conductive agent graphite, 4wt% conductive agent acetylene black, 3wt% binder polyvinylidene fluoride, 3wt% binder polytetrafluoroethylene, 3wt% additive calcium oxide, and 3wt% additive silicon dioxide. The 1A discharge curve of AA-type lithium-iron disulfide battery prepared by the lithium-iron disulfide positive electrode sheet of this embodiment is as follows: Figure 1 , Figure 2It shows that the composite active material can improve the discharge platform of lithium-iron disulfide battery and appropriately improve the capacity.

[0021] Example 2

[0022] Preparation of composite active material: add cobalt disulfide and ferrous sulfate heptahydrate with a mass ratio of 1:15 in a beaker, add an appropriate amount of deionized water and stir evenly, slowly add 15% sodium persulfide solution during stirring, soak and wash the precipitate after centrifugation of the mixture with deionized water for 3 times, and dry at 70°C to obtain an active material intermediate. The intermediate is heated to 500°C in an argon atmosphere for 20 hours, and naturally cooled and sieved to obtain iron disulfide coated with cobalt disulfide with an average particle size of 12 to 15 μm, i.e., a composite active material.

[0023] The lithium-iron disulfide positive electrode sheet was prepared according to the method described in Example 1. The 1A discharge curve of the AA-type lithium-iron disulfide battery prepared by the lithium-iron disulfide positive electrode sheet of this example is similar to Figure 1 , which has been omitted, indicates that the composite active material can improve the discharge platform of lithium-iron disulfide batteries and can appropriately improve the capacity.

[0024] Example 3

[0025] Preparation of composite active material: add cobalt disulfide and ferrous sulfate heptahydrate with a mass ratio of 1:20 with a particle size of 2 to 5 μm in a beaker, add an appropriate amount of deionized water and stir evenly, slowly add 15% sodium persulfide solution during stirring, soak and wash the precipitate after centrifugation of the mixture with deionized water for 3 times, and dry at 70°C to obtain an active material intermediate. The intermediate product is heated to 500°C in an argon atmosphere for 20 hours, and naturally cooled and sieved to obtain iron disulfide coated with cobalt disulfide with an average particle size of 12 to 15 μm, i.e., a composite active material.

[0026] The lithium-iron disulfide positive electrode sheet was prepared according to the method described in Example 1. The 1A discharge curve of the AA-type lithium-iron disulfide battery prepared by the lithium-iron disulfide positive electrode sheet of this example is similar to Figure 1 , which has been omitted, indicates that the composite active material can improve the discharge platform of lithium-iron disulfide batteries and can appropriately improve the capacity.

[0027] Example 4

[0028] Preparation of composite active material: add cobalt disulfide and ferrous sulfate heptahydrate with a mass ratio of 1:20 in a beaker, add an appropriate amount of deionized water and stir evenly, slowly add 20% sodium persulfide solution during stirring, soak and wash the precipitate after centrifugation of the mixture with deionized water for 3 times, and dry at 70°C to obtain an active material intermediate. The intermediate is heated to 500°C in an argon atmosphere for 20 hours, and naturally cooled and sieved to obtain iron disulfide coated with cobalt disulfide with an average particle size of 12 to 15 μm, i.e., a composite active material.

[0029] The lithium-iron disulfide positive electrode sheet was prepared according to the method described in Example 1. The 1A discharge curve of the AA-type lithium-iron disulfide battery prepared by the lithium-iron disulfide positive electrode sheet of this example is similar to Figure 1 , which has been omitted, indicates that the composite active material can improve the discharge platform of lithium-iron disulfide batteries and can appropriately improve the capacity.

[0030] Comparative Example 1

[0031] Active material: Iron disulfide with a particle size of 12 to 15 μm

[0032] Preparation of positive electrode sheet of lithium-iron disulfide battery: The positive electrode slurry and positive electrode current collector are coated by a coating machine, and then baked, rolled, cut, and welded to form positive electrode sheet. The positive electrode slurry is composed of 78wt% active material, 6wt% conductive agent graphite, 4wt% conductive agent acetylene black, 3wt% binder polyvinylidene fluoride, 3wt% binder polytetrafluoroethylene, 3wt% additive calcium oxide, and 3wt% additive silicon dioxide. The 1A discharge curve of the AA-type lithium-iron disulfide battery prepared by the lithium-iron disulfide positive electrode sheet of this comparative example is as follows: Figure 1 As shown, it is shown that the composite active material of Example 1 can improve the discharge platform of the lithium-iron disulfide battery and can appropriately improve the capacity.

[0033] Comparative Example 2

[0034] Active material: Cobalt disulfide with a particle size of 2 to 5 μm

[0035] Preparation of positive electrode sheet of lithium-cobalt disulfide battery: The positive electrode slurry and positive electrode current collector are coated by a coating machine, and then baked, rolled, cut, and welded to form positive electrode sheet. The positive electrode slurry is composed of 78wt% active material, 6wt% conductive agent graphite, 4wt% conductive agent acetylene black, 3wt% binder polyvinylidene fluoride, 3wt% binder polytetrafluoroethylene, 3wt% additive calcium oxide, and 3wt% additive silicon dioxide. The 1A discharge curve of AA-type lithium-cobalt disulfide battery prepared by the lithium-cobalt disulfide positive electrode sheet of this comparative example is as follows: Figure 2 As shown, it is shown that the composite active materials of Examples 1-4 can improve the battery capacity.

[0036] The difference between Comparative Examples 1-2 and Examples 1-4 is that the active material of Comparative Example 1 is iron disulfide, the active material of Comparative Example 2 is cobalt disulfide, and the active material of Examples 1-4 is a composite active material of iron disulfide coated with cobalt disulfide.

[0037] The positive electrode sheets in Examples 1 to 4 and Comparative Examples 1 to 2 were assembled into AA batteries and tested for electrical properties and storage performance. The test results are shown in Table 1, Table 2 and Table 3:

[0038] Table 1 Comparison of AA battery internal resistance and pulse discharge times

[0039]

[0040] Table 2 Comparison of constant current discharge capacity of AA type batteries

[0041]

[0042] Table 3 Comparison of discharge capacity of AA-type batteries when new and stored at 70℃ for 100 days

[0043]

[0044]

[0045] By comparing the various electrical performance data of Examples 1 to 4 and Comparative Examples 1 to 2 in Tables 1 to 3, it is found that the lithium-iron disulfide battery using the composite active material of the present invention has low internal resistance and excellent storage performance, and also improves the discharge platform of the battery and the pulse discharge performance of the battery, indicating that the composite active material of the present invention can effectively improve the electrical performance and storage performance of the lithium-iron disulfide battery.

[0046] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A composite active material, which is a core-shell structure of cobalt disulfide and iron disulfide, characterized in that: The core-shell structure is iron disulfide coated with cobalt disulfide, the particle size of the cobalt disulfide is 2-5 μm, and the particle size of the composite active material is 12-20 μm.

2. A method for preparing the composite active material according to claim 1, comprising the steps of: a. Add deionized water to cobalt disulfide and ferrous sulfate heptahydrate in a mass ratio of 1 to 2:10 to 25 and stir evenly. Add 10 to 30% by weight of sodium persulfide solution during stirring. After centrifugation, the precipitate of the mixture is soaked and washed 2-4 times with deionized water and dried at 60-80°C to obtain an active material intermediate; b. The intermediate product is heated to 400-500° C. in an argon atmosphere for 16-20 hours, and after natural cooling, is sieved to obtain an iron disulfide composite active material with a particle size of 12-20 μm and coated with cobalt disulfide.

3. The method for preparing a composite active material according to claim 2, wherein the mass ratio of cobalt disulfide to ferric sulfate heptahydrate in step a is 1:10-20.

4. The method for preparing a composite active material according to claim 3, wherein the weight percentage of the sodium persulfide solution in step a is 10-20%.

5. The method for preparing a composite active material according to claim 4, characterized in that: in the step a, the precipitate after centrifugation of the mixture is soaked and washed three times with deionized water, and then dried at 70°C to obtain an active material intermediate product; in the step b, the intermediate product is heated to 500°C in an argon atmosphere for 20 hours, naturally cooled, and sieved to obtain an iron disulfide composite active material with a particle size of 12 to 20 μm and coated with cobalt disulfide.

6. A lithium-iron disulfide battery positive electrode plate, characterized in that it comprises an active conductive material, a conductive agent, a binder and a positive electrode additive, wherein the active conductive material is the composite active material as claimed in claim 1.

7. The lithium-iron disulfide battery positive electrode according to claim 6 is characterized in that: its weight percentage is composed of 70-88wt% active conductive material, 4-10wt% conductive agent, 4-10wt% binder and 4-10wt% positive electrode additive.

8. The lithium-iron disulfide battery positive electrode sheet according to claim 7 is characterized in that: its weight percentage is composed of 78wt% active conductive material, 10wt% conductive agent, 6wt% binder and 6wt% positive electrode additive.

9. The positive electrode of a lithium-iron disulfide battery according to claim 8, wherein the conductive agent is at least one of carbon nanotubes, graphite, graphene, graphite worms, Ketjen black and acetylene black.

10. The lithium-iron disulfide battery positive electrode according to claim 9, characterized in that: the binder is at least one of polyvinylidene fluoride, polytetrafluoroethylene, polyacrylonitrile, carboxymethyl cellulose, polyimide and polyacrylate; the positive electrode additive is at least one of glutaric anhydride, glycerol sulfite, ethylene sulfate, calcium oxide and silicon dioxide.